PENGARUH KERAGAMAN PRODUK, PERSEPSI HARGA, DAN KUALITAS LAYANAN TERHADAP KEPUASAN ( Studi pada Konsumen Jasa Pengiriman Paket POS di Semarang) - Nurul Hidayah, 15.05.51.0065; Tjahjaningsih, Endang (Students' Journal of Economic and Management, 2019)
This study aims to examine the effect of product diversity, price perception, and service quality on customer satisfaction. This research was conducted on all consumers of POS package delivery services in Semarang. The samples used in this study were 98 POS respondents in Semarang. The sampling method uses purposive sampling The data used is primary data. Analysis of the data used includes the validity, reliability, multiple linear regression test, determination coefficient (R2), F test and hypothesis test. The results of this study indicate that product diversity variables have a positive and significant effect on customer satisfaction. Variable price perception has a negative and not significant effect on customer satisfaction. Service quality variables have a positive and significant effect on customer satisfaction.